Analysis of Consumer Behavior on Purchasing Decisions at Assalam Hypermarket through Customer Purchase Interest - Bella Febrianti; Purnamaningtyas Kusuma Dewi; Yuliana Subastine (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to analyze the effect of consumer behavior on purchasing decisions at Assalam Hypermarket with purchase intention as a mediating variable. The study uses a quantitative approach with an explanatory research method. The research population consists of customers and visitors to Assalam Hypermarket with a sample size of 150 respondents selected through purposive sampling. Primary data were collected through questionnaires and analyzed using the Partial Least Square Structural Equation Modeling (PLS-SEM) method with SmartPLS software. The results show that consumer behavior has a positive and significant effect on purchase interest, as well as a positive and significant effect on purchasing decisions. In addition, purchase interest also has a positive and significant effect on purchasing decisions. Another important finding is that purchase intention significantly mediates the relationship between consumer behavior and purchase decisions. This study confirms that positive consumer behavior can encourage an increase in purchase decisions, both directly and indirectly through the role of purchase intention. The results of this study are expected to provide strategic input for the management of Assalam Hypermarket in improving marketing strategies and strengthening customer loyalty